Revitalizing the Deliberative Function of Political Parties within Indonesia’s Substantive Democracy - Noer, Hamka Hendra (Journal of Government Science Studies, 2025)
In the last two decades, discussions surrounding deliberative democracy have significantly increased the rational dialogue, equitable participation, and the cultivation of reflective public opinion in the realm of political decision-making. Nonetheless, the current academic literature has largely ignored the role of political parties as institutional actors that bridge the gap between the government and society. This article addresses this oversight by critically examining the substantive role of political parties within the context of deliberative democracy, along with proposing avenues for institutional reform aimed at fostering a more inclusive democratic process. Through a comprehensive analytical method of literature review and cross-country comparisons, this study investigates the deliberative capacities of political parties in the United States, Europe (with particular emphasis on Germany and Scandinavia), and Indonesia. The findings indicate that European political parties have been relatively successful in integrating public discourse forums into their internal frameworks, whereas in the United States, the process of deliberation is frequently obstructed by ideological polarization and economic hegemony. On the other hand, Indonesia encountered patronage politics, weak institutionalization, and a transactional political culture as their main challenges. The study concludes that the absence of a robust internal deliberative infrastructure substantially contributes to the crisis of party representation. This research emphasises on reintegrating the role of political parties as facilitators of public discourse, rather than relegating them to the status of mere electoral machines. Strategic recommendations include the implementation of internal structural reforms, the development of idea-driven party cadres, and the fostering of stronger partnerships with civil society to enhance substantive democracy.